AUDIT TEKNOLOGI INFORMASI MENGGUNAKAN COBIT UNTUK MENGUKUR KINERJA AKUNTANSI BERBASIS TEKNOLOGI INFORMASI (Studi Kasus: PT. BALINA AGUNG BEKASI) - Haryani Haryani (Jurnal Informatika dan Bisnis, 2016)
IT Governance is a structure of relationships and processes to direct and control an organization to achieve its goals by adding value while balancing risk compared to IT and process. To improve IT governance good it would require an evaluation in the process of IT management, the measurement of IT governance maturity level at this time, and made some recommendations for improvement of IT governance in Balina Agung PT Bekasi. Analysis for IT governance in Balina Agung PT Bekasi carried out to analyze the management of information and communications technology to see the conditions that exist today, assess and measure the maturity level of IT management, and to determine the extent to which IT management is expected in the future, then made a recommendation for the improvement of IT management in accordance with the objectives and strategy of the company. IT governance analysis in this study uses a framework COBIT (Control Objective For Information and Related Technology) version 4.0 is a standard model that provides documentation of best practice IT management can help the management and users to bridge the gap between business risk, control needs and technical issues. The research is descriptive quantitative research that is by looking for information on information and com munication systems and take measurements of the level of maturity of IT governance, especially at PO domains (Planning and Organization) and AI (Acquisition and Implementation). Does the application of information and communication technology is in conformity with the vision, mission and objectives of the company. Currently, the maturity level for each existing process on the PO domain (Planning and Organization) and AI (Acquisition and Implementation) is almost as a whole in level 2. It is suggested that the evaluation of IT governance can be done routinely every certain period of time (periodic), so that the desired level of maturity can be achieved and carried out by specialized units.Key words: Audit of Information Technology, Accounting Performance, COBIT